Exploring music therapy for Filipino autistic children. [article]. - Marin, Marisa V.
This study explored the use of music therapy as a means to enhance the therapeutic processes with autistic Filipino children. Using a clinical descriptive and phenomenological approach, five autistic children were purposively selected to attend 12 individual music therapy sessions. Findings show that music therapy can be considered as a therapeutic intervention for children with autism because it addresses their primary concerns such as making connections, developing eye contact and verbalization, facilitating expression of feelings and modifying stereo-typic behaviors.